“Evaluación de medios de cultivo en la propagación in vitro de caña de azúcar (saccharum offinarum) a partir de meristemos” - Arévalo Armas, Francisco (2005)
The present investigation work one carries out in the laboratory of cultivation of Fabrics vegetables of the National University of San Martin - Tarapoto, with 1 title ""Evaluation of Means of Cultivation in the Propagation In Vitro of Cane of Sugar (Saccharum officinarum) starting from Meristemos", likewise he/she had as objectives: To develop an efficient protocol for the meristemos differentiation and to evaluate the efficiency of the on means in study. The used design was Experimental Design Totally at random with 4 treatments but a witness and 10 observations. The treatments were TO (M&S), T1 (Heinz and Urinate), T2 (Payan and Tarcon), T3 (H.S.P.A) ANO T4 (Salazar and Surga). The results demonstrated that the meristemos a week of being sowed in the means had already differed, since the treatment that but he/she responded the T3 for that one could obtain complete and vigorous plántulas since him means was he/she had a balanced balance of hormones what allowed that the meristemos is usually developed. But it is necessary to mention that the contamination and fenolización were a parameter in which one had problems, since to the dome meristematico when making the perpendicular cut is oxidized since he/she has polifenoles and the contamination is another factor to keep in mind to the moment to make the siembra in the respective means.